The influence of yttrium on a typical SnO2 varistor system: Microstructural and electrical features - Parra, R.; Maniette, Y.; Varela, José Arana [UNESP]; Castro, M. S. (Elsevier B.V., 2005)
The influence of yttrium oxide, Y2O3, on the microstructure development of the SnO(2)center dot Co(3)O(4)center dot Nb2O5 typical varistor system was studied with scanning (SEM) and transmission (TEM) electron microscopies. The different phases present in the studied samples were characterized through XRD, EDS and selected area diffraction patterns (SAD). Particles of Co2SnO4 were observed with TEM in every sample, whereas clusters of the pyrochlore phase T2Sn2O7 were observed with SEM in samples with 0.05, 0.10 and 0.25 mol% of Y2O3. The higher non-linearity (a = 16) was achieved with the addition of 0.05 mol% of Y2O3. The influence of the secondary phases on the electrical properties is also addressed in this work. (c) 2005 Published by Elsevier B.V.
Keywords: varistors; electron microscopy; electrical properties; SnO2